Effectiveness Of Education in the Training of Specialists of Alternative Energy Sources (Solar and Energy) on the Basis of Innovative Technologies of Education - Yuldashev Farrukhjon Murod o'g'li; Yuldashev Javohir Murod o'g'li (Genius Journals, 2022)
The widespread use of alternative energy sources is in line with the priorities and energy security objectives of each country and is one of the fastest growing areas of the energy sector. Certain work is being carried out in the country on the development of renewable energy sources, first of all, the use of hydro power potential. Decree of the President of the Republic of Uzbekistan No. PQ-4512 of 01.03.2013 "On measures for further development of alternative energy sources" and 01.03.2013 "On the establishment of the International Solar Energy Institute" The Institute of Solar Energy was established on the basis of the Physics-Sun Scientific Production Association as part of the implementation of the Resolution No. PP-1929. SJSC "Uzbek energy" is one of the founders of this institute.
Keywords: Energy; wind; solar; expert